Income comparisons, income adaptation, and life satisfaction: How robust are estimates from survey data? - Tobias Pfaff (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2013)
Theory suggests that subjective well-being is affected by income comparisons and adaptation to income. Empirical tests of the effects often rely on self-constructed measures from survey data. This paper shows that results can be highly sensitive to simple parameter changes. Using large-scale panel data from Germany and the UK, I report cases where plausible variations in the underlying income type substantially affect tests of the relationship between life satisfaction, income rank, reference income, and income adaptation. Models simultaneously controlling for income and income rank as well as models with a number of income lags are prone to imperfect multicollinearity with consequences for the precision and robustness of estimates. When testing relative-income effects, researchers should be aware that reference income constructed as average of a rather arbitrarily defined reference group and reference income predicted from Mincer-type earnings equations are two approaches that can produce inconsistent results, and that are probably not as reliable and valid as previously assumed. The analysis underlines the importance of robustness checks and regression diagnostics, two routines that are often not carried out diligently in empirical research. – – Der Theorie nach wird subjektives Wohlbefinden von Einkommensvergleichen und Einkommensanpassungseffekten beeinflusst. Empirische Tests dieser Effekte verwenden oft selbstkonstruierte Messgrößen aus Umfragedaten. Dieser Artikel zeigt, dass Ergebnisse sehr sensitiv gegenüber einfachen Parameterveränderungen sein können. Unter Verwendung großer Paneldatensätze aus Deutschland und Großbritannien zeige ich Fälle, in denen plausible Veränderungen der zugrundeliegenden Einkommensart substantiellen Einfluss auf Tests des Zusammenhangs zwischen Lebenszufriedenheit, Einkommensrang, Referenzeinkommen und Einkommensanpassung haben. Modelle die simultan für Einkommen und Einkommensrang kontrollieren sowie Modelle mit einigen Lags der Einkommensvariable sind anfällig für imperfekte Multikollinearität mit entsprechenden Konsequenzen für Präzision und Robustheit der Schätzer. Forscher sollten bei Tests von relativen Einkommenseffekten darauf achten, dass Referenzeinkommen konstruiert als Durchschnitt einer recht willkürlich definierten Referenzgruppe sowie Referenzeinkommen, das mit einer Lohngleichung des Mincer-Typs prognostiziert wird, zwei Ansätze sind, die inkonsistente Ergebnisse liefern können und daher möglicherweise nicht so verlässlich und valide sind, wie bislang angenommen. Die Analyse unterstreicht die Bedeutung von Robustheitschecks und Regressionsdiagnostik - zwei Routineprozesse, die in empirischen Studien oft nicht gründlich durchgeführt werden.
Keywords: 330; subjective well-being; life satisfaction; relative income; income rank; adaptation; subjektives Wohlbefinden; Lebenszufriedenheit; relatives Einkommen; Einkommensrang; Adaptation